Digital Devices Use and Language Skills in Children between 8 and 36 Month - Francesca Felicia Operto (Brain Sciences, 2020)
on: In our study we found that a longer time of exposure to digital devices was related to lower mimic-gestural skills in children from 8–17 months and to lower language skills in children between 18 and 36 months, regardless of age, gender, socio-economic status, content, and modality of use. Further studies are needed to confirm and better understand this relation, but parents and pediatricians are advised to limit the use of digital devices by children and encourage the social interaction to support the learning of language and communication skills in this age group.